The Influence of Influencer Credibility, Brand Image, and Ad Relevance on Purchase Intent for Beauty Products (A Study of Somethinc Product Promotions Via Influencer Tasya Farasya) - Tanesa, Leslie Natalie; Daniel, Joseph Robert (Journal Research of Social Science, Economics, and Management, 2026)
Influencer marketing has become a dominant strategy in digital beauty brand promotion, yet the relative contribution of influencer credibility, brand image, and ad relevance to consumer purchase intention remains underexplored, particularly when these constructs are examined simultaneously within a single framework. This study investigates the partial and simultaneous effects of these three variables on purchase intention, using the collaboration between Indonesian beauty brand Somethinc and influencer Tasya Farasya on TikTok and Instagram as its empirical context. A quantitative explanatory approach was employed, with data collected from active social media users in Surabaya selected through purposive sampling and analyzed using multiple linear regression with SPSS. The findings reveal that brand image and ad relevance each exert a significant positive effect on purchase intention, while influencer credibility does not demonstrate a meaningful direct effect when considered independently. Simultaneously, all three variables together account for a substantial proportion of the variance in consumer purchase intention, confirming the significance of the integrated model. These results suggest that marketers should prioritize building a strong, consistent brand image and delivering contextually relevant content, rather than relying primarily on influencer popularity. This study contributes to the literature by integrating three constructs previously studied in isolation into a more comprehensive conceptual framework applicable to social media influencer marketing in Indonesia.